Respiratory Care Work Assignment Based on Work Rate Instead of Work Load. - Chatburn, Robert L.; Gole, Susan; Schenk, Philip; Hoisington, Edward R.; Stoller, James K. (Respiratory Care, 2011)
BACKGROUND: We previously reported a new management variable, work rate, defined as work load due per hour, based on cumulative standard treatment times. We found that work rates were unachievable (ie, exceeded 1 hour of scheduled work per hour of available labor) for 75% of scheduled due times, despite presumed achievable average work load. OBJECTIVE: To determine the optimal strategy for creating work assignments based on work rate. METHODS: A focus group used root-cause analysis to identify ways to balance assignments based on work rate. We surveyed employees to assess their willingness to start earlier. We determined the ratio of scheduled to unscheduled work during a 12-month period. The scheduled work comprised administering small-volume nebulizer, metered-dose inhaler, noninvasive ventilation, and mechanical ventilation. The unscheduled work consisted of all other modalities. We also developed a spreadsheet model to assess the effect of shifting the start time on work-rate distribution in a representative 24-hour period. RESULTS: The focus group determined that starting treatments 1 hour earlier would help. Fifteen of the 24 clinicians surveyed responded, and 13 of the respondents were willing to start earlier. The scheduled work load averaged approximately 55% of the total work load, but there was high variability per assignment area (range 0-99%). The spreadsheet model showed that shifting treatment start times improved the distribution of work rate throughout the day, but did not guarantee that labor demand never outstrips supply. CONCLUSIONS: Our studies to date suggest that: basing assignments on average work load leads to periods of unachievable work rate, resulting in missed treatments and staff dissatisfaction. We have only limited ability to reduce peaks in work rate, but staggering treatment times is effective. Fair assignment of work should differentiate scheduled from unscheduled work.